The role of second‐hand smoke exposure on smoking cessation in non–tobacco‐related cancers. Issue 15 (15th April 2015) - Eng, Lawson; Qiu, Xin; Su, Jie; Pringle, Dan; Niu, Chongya; Mahler, Mary; Charow, Rebecca; Villeneuve, Jodie; Halytskyy, Oleksandr; Lam, Christine; Tiessen, Kyoko; Brown, M. Catherine; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Second‐hand smoke (SHS) is a significant barrier to smoking cessation after a diagnosis of cancer in patients with lung as well as head and neck cancers. In the current study, the authors evaluated the effect of SHS on smoking cessation among patients with those cancers not traditionally perceived to be strongly associated with smoking. METHODS Patients recruited from a single tertiary care center completed a self‐administered questionnaire. Multivariate logistic regression and Cox proportional hazards models evaluated the association of sociodemographics, clinicopathological variables, and exposure to SHS with either smoking cessation or time to quitting. RESULTS In all, 926 patients with diverse cancer subtypes completed the questionnaire. Of the 161 who were current smokers at the time of their cancer diagnosis, 48% quit after diagnosis. Lack of exposure to SHS at home was found to be associated with smoking cessation at any time after diagnosis (adjusted odd ratio, 4.28; 95% confidence interval, 1.56‐11.78 [P =.005]), with similar trends noted 1 year after diagnosis (adjusted odds ratio, 2.56; 95% confidence interval, 0.91‐7.22 [P =.08]). There was a significant inverse dose‐response relationship between hours of SHS exposure at home and smoking cessation. Spousal and peer smoking were not found to be significantly associated with smoking cessation on multivariate analysis (P>.05). Kaplan‐Meier analysis found that of patients who did quit smoking, 61% quit within 6 months of their cancer diagnosis. CONCLUSIONS Exposure to SHS at home is a significant barrier to smoking cessation in patients whose cancers are not traditionally perceived as being related to tobacco. SHS should be a key consideration in the development of survivorship programs geared toward smoking cessation for all patients with cancer. Cancer 2015;121:2655–2663. © 2015 American Cancer Society.